BiS2-Layer Gives Giant Birefringence: First-Principles Calculations. (May 2016) - Wang 王, Hai 海
Abstract : Birefringence attracts increasing attention due to its extensive applications in the imaging spectrometer, laser devices and optical components. Stimulated by the discovery of the giant birefringence (GBF) in LaOBiS2 and AFBiS2, we explore its origin by checking three compounds with and without the BiS2 layer: Bi2 OS2 (i.e., BiOBiS2 ), Bi2 O2 S and LaOAlS2 . It is demonstrated that GBF appears only in the compounds with the BiS2 layer and is furthermore confirmed in MOBiS2 (M=Al, Ga, In and Sc) compounds. The result is useful for discovering/developing new-type birefringent crystal or even multifunctional materials.